Breast cancer: carcinogenesis, diagnosing and treatment - de Souza Albernaz, Marta; Santos do Carmo, Fagner; Helal-Neto, Edward; dos Santos Nascimento, Sofia; Santos-Oliveira, Ralph (European Journal of Oncology and Environmental Health, 2017)
Breast cancer is the most common and deadly type of cancer that affects women worldwide.  A good anamnesis, allied with a highly accurate diagnosis and a correct interpretation of the data acquired relies the best chance for the patient to receive the best treatment and, in this direction, improve the chance of cure and/or better prognosis. In all the cases, a good theoretical basis is fundamental. Thus, this update review intend to be a primary source on Breast Cancer, paving and consolidating knowledge in the field of breast cancer and helping physicians in their daily difficult task to deal with this disease.